(untitled) (Research, Society and Development, 2021)
The investigation whose results we bring in this article sought to analyze the transformation of a Pedagogical Course Project, from the 2014 version to the 2018 version, of a Integrated High School, belonged to a campus of the Federal Institute of Paraná, Brazil. The aim of the research was to understand, from the conception of the Actor-Network Theory, the socio-educational aspects that influenced this transformation. Such Theory was assumed as a theoretical and methodological reference and made it possible to observe the social as a result of the relationship between humans and non-humans (actants) and how the controversies happened around a non-human, the PPC. Through the procedures indicated by the Content Analysis, we used fragments of protocols, interviews and reports to highlight controversies that were categorized as follows: methodology; training; autonomy; evaluation, and the formation of networks of actors in relation to which we dedicate ourselves to observe some elements: federal government; student; pedagogical proposal; teacher. The result was presented in the form of a documented report that shows the path from PPC2014 to PPC2018 and that led us to conclude that the existence of an actor is only possible in its support network. In the case analyzed, PPC2014 was not consolidated because it did not find a network to support it and, therefore, PPC2018 was the result of the network available in that context. A fact that led us to consider that the more peculiar the Pedagogical Course Projects are, the more specific the constituents of its support network will be.